The Role of Carboxyl and Hydroxyl Groups of Humic Acid in Removing AuCl4- from Aqueous Solution - Sri Sudiono; Mustika Yuniarti; Dwi Siswanta; Eko Sri Kunarti; Triyono Triyono; Sri Juari Santosa (Indonesian Journal of Chemistry, 2017)
Humic acid (HA) extracted from peat soil according to the recommended procedure of the International Humic Substances Society (IHSS) has been tested to remove AuCl4- from aqueous solution. The removal was optimum at pH 2.0 and it was mainly dictated by attachment through hydrogen bonding to unionized carboxyl (–COOH) groups and reduction by the action of the hydroxyl (–OH) groups to gold (Au) metal. The removal of AuCl4- improved after HA was purified through repeated immersion and shaking in a mixed solution containing 0.1 M HCl and 0.3 M HF. When the purification led to the sharp decrease in ash content from 39.34 to 0.85% (w/w) and significant increase in both the –COOH and –OH contents from 3240 to 3487 mmol/kg and from 4260 to 4620 mmol/kg, respectively; the removal of AuCl4- improved from 0.105 to 0.133 mmol/g. This improvement of AuCl4- removal by the purified HA was accompanied by higher ability in reduction to Au metal. The attached AuCl4- on –COOH groups of both crude and purified HAs was qualitatively observed by the characterization result of FT-IR spectroscopy, while the presence of Au metal on the surface of those HAs was verified by the characterization result of XRD.